Further Investigation on the Relaxed Hybrid Steepest-Descent Methods for Variational Inequalities with k-Strict Pseudocontractions - Qian-Fen Gong; Dao-Jun Wen (Journal of Applied Mathematics)
We modify the relaxed hybrid steepest-descent methods to the case of variational inequality for finding a solution over the set of common fixed points of a finite family of strictly pseudocontractive mappings. The strongly monotone property defined on cost operator was extended to relaxed cocoercive in convergence analysis. Results presented in this paper may be viewed as a refinement and important generalizations of the previously known results announced by many other authors.